Study of Snack Pattern and Some Factors Affecting It among Elementary School Students in the Gonbad, Iran - Qasem Abedi; Nasibe Zerangian; Mehran Asadi-Aliabadi; Fereshteh Rostami-Maskopaee (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Healthy nutrition is an important factor in student learning and educational achievement. The present study aimed to survey snack pattern and some of its associated factors among students in elementary schools of Gonbad city, Iran, during 2013-2014. Methods: This cross-sectional study was performed in 245 students from eight elementary schools (both state and independent) of Gonbad city, Iran. The participants were chosen through multistage sampling method; in doing so, first Gonbad city was divided into four regions. The subjects were selected after selecting a random sample of schools in each region proportionate to the size of the region. Data was collected through a checklist consisting of two parts of demographic data and consumed snacks, which were collected by health experts. To analyze the data, Chi-squared test and Spearman’s rank-order correlation were used in SPSS, version 17. Results: The mean age of the students was 10.3±1.4 years. About 97.7% of the students consumed snack. Biscuits, cakes, and cookies were the most frequently consumed snacks (49%). Moreover, a significant relationship was found between snack consumption and maternal age (P<0.045), maternal educational level (P<0.001), and birth order of the students (P<0.045). Conclusion: Despite the favorable status of snack consumption in students, more attention should be drawn to the type of materials used in snacks. Given the importance of consumption of breakfast and snack in students, we recommend implementing training programs for students as to the importance of eating snacks.